(untitled) (Research, Society and Development, 2020)
Objective: The objective of this study is to analyze in the literature, through an integrative review, how is the condition of health and oral hygiene of indigenous patients living in Brazil. Methodology: This is an integrative review methodology carried out in February and March 2020, through the acquisition of scientific data from the platforms (SciELO), National Library of Medicine (PubMed) and Latin American and Caribbean Literature in Sciences of Health (Lilacs). The selected articles were published between 2010 and 2020, in Portuguese and English. To find the articles, the following descriptors were used: “Dentistry”, Oral Health”, Health Indigenous Service”, carried out several searches with the descriptors individually and soon after the crossings with the descriptors were made, using the “AND” Boolean browser. Results: For the construction of this integrative review, eight scientific articles were explored that met the inclusion and exclusion criteria previously defined. Conclusion: Therefore, it is necessary to reach a greater range of promotional and preventive programs in oral health, in order to disseminate the practice of hygiene and oral care and encourage the search for dental care.